Risk factors for bronchial hyperresponsiveness in workers exposed to acid anhydrides. - Barker, R; van Tongeren, M; Harris, J; Gardiner, K; Venables, K; Newman Taylor, A (2000)
Risk factors for bronchial hyperresponsiveness have previously been established in the general community. In settings where occupational asthma is a risk, it has not been established whether occupational sensitization or measures of exposure are important. Bronchial responsiveness to histamine was measured in a cohort of 506 workers exposed to acid anhydrides. Skin-prick tests were performed with conjugates of phthalic, maleic and trimellitic anhydride with human serum albumin and with common inhalant allergens. Employment and smoking histories were recorded. Occupational exposure was measured using personal air samplers and estimates of past exposure made by retrospective exposure assessment. Three hundred and seventy workers (73%) had bronchial responsiveness measured (median age 39 yrs, range 18-77) and 46 (12%) of these were hyperresponsive (provocative dose causing a 20% fall in forced expiratory volume in one second (FEV1; PD20) < or = 8 micromol). Twelve (3%) of these responsive workers had a skin-prick test reaction to an acid anhydride conjugate, 124 (34%) to a common inhalant allergen, and 148 (40%) were current smokers. Multivariate analysis showed that occupational sensitization, sensitization to a common inhalant allergen, age, and pack-years of smoking were independent risk factors for bronchial hyperresponsiveness. Of these only occupational sensitization was completely independent of baseline FEV1. It is concluded that sensitization to acid anhydrides is a significant risk factor for bronchial hyperresponsiveness. However, measures of personal acid anhydride exposure were not associated with bronchial hyperresponsiveness.